Identification of differentially expressed gene/s observed in stem cells derived extracted human tooth - Mokhtar, Khairaniidah (Universiti Sains Malaysia, 2012)
The aim of this study was to identify the differentially expressed genes (DEGs) in SHED and DPSCs by GeneFishing™ DEG method using the arbitrary primer pairs provided. Two bands which were highly expressed in SHED and three bands in DPSCs were isolated purified and sent for sequencing. Sequencing analysis revealed these to be TIMP Metallopeptidase Inhibitor 1 (TIMP1}, (A09), and ribosomal protein s8, (RPS8), (A16) in SHED and collagen, type I, alpha 1, (COL1AP), (A20), follistatin-like 1 (FSTL1), (A17), lectin, galactosidebinding, soluble, 1, (LGALSP), (A16) in DPSCs. TIMP1 is involved in degradation of the extracellular matrix, cell proliferation and anti-apoptotic function and RPS8 is involved as a rate-limiting factor in translational regulation; COL1A1 is involved in the resistance and I elasticity of the tissues; FSTL1 is an autoantigen associated with rheumatoid arthritis; LGALS1 is involved in cell growth, differentiation, adhesion, RNA processing, apoptosis, and malignant transformation. The gene expression patterns of SHED and DPSCs might be useful in determining the detailed functional roles of the relevant genes applicable to stem cell therapies, which paves way to be used as I multipotent cell sources for genetic and tissue engineering technology.